Concerns about body shape and weight in the postpartum period and their relation to women's self-identification - Patel, P; Lee, J; Wheatcroft, R; Barnes, J; Stein, A (2005)
The purpose of this qualitative study was to examine how three groups of women, with different levels of eating disorder psychopathology, perceived and coped with changes in eating and body shape and weight following pregnancy and the birth of a baby. Furthermore, we aimed to find out how such changes influenced their identity as mothers. Twenty-one mothers were selected from a large survey of women's eating habits and attitudes in the postnatal period: mothers with an eating disorder (n=6), mothers who were at risk for eating disorder (n=9) and a comparison group without such concerns (n=6). They were interviewed in detail about their eating habits and attitudes to body shape and weight and a variety of related issues. Thematic analyses of the transcripts identified five themes: (i) loss of the pre-pregnancy self; (ii) life transitions; (iii) feeding relationship with infant; (iv) new relationship with family members; and (v) role within wider society. Differences were identified between the groups. For example, mothers with eating disorders tended to perceive the external world as more negative and critical about their new maternal selves. Mothers in the comparison group seemed better able to 'prioritize' and tolerate their baby's dependency on their bodies, discussing breastfeeding in relation to infant needs rather than their own body needs. Comparison mothers were also more able to reflect on the implications of the changes in shape (and loss of their former slim selves). The findings suggest that the postnatal period may be a vulnerable time for mothers with eating difficulties. Previous life transitions seemed to be relevant to this life-changing transition. © 2005 Society for Reproductive and Infant Psychology.